Handgrip strength asymmetry and cognitive impairment risk: Insights from a seven-year prospective cohort study - Tao-Chun Peng; Jeng-Min Chiou; Yen-Ching Chen; Jen-Hau Chen (Elsevier, 2024)
Objectives: This study aimed to explore the links of handgrip strength and asymmetry with cognitive impairment. Design: This was a seven-year prospective cohort study. Setting and participants: We used data from wave 3 (2015-2017) to wave 5 (2019-2022) from the ongoing Taiwan Initiative of Geriatric Epidemiological Research (TIGER), with wave 3 as the baseline (n = 446). The study included community-dwelling participants aged 65 years or older. Measurements: Handgrip strength was measured, and abnormalities were determined based on handgrip strength weakness and asymmetry. Handgrip strength asymmetry was categorized into three groups at baseline based on the handgrip strength ratio (left handgrip strength/right handgrip strength). Cognitive tests evaluating global and specific cognitive domains were conducted at baseline and two biennial follow-ups. Generalized linear mixed models were utilized to assess the associations of abnormal handgrip strength with global cognition and multiple cognitive domain progression over time. Results: This study included 392 dementia-free participants, with an average age of 75.8 years and 179 (45.7%) males. Mild handgrip strength asymmetry was present in 88 participants (22.4%), while 53 (13.5%) exhibited moderate asymmetry. In men, the coexistence of low handgrip strength and handgrip strength asymmetry was linked to cognitive impairment over time. These associations were observed in global cognition (β^ = −1.76, 95% CI: −2.79 to −0.74), memory (immediate free recall: β^ = −0.67, 95% CI: −1.17 to −0.17), executive function (Trail Making Test-A: β^ = −0.54, 95% CI: −0.94 to −0.13), and attention (Digit span-forward: β^ = −1.00, 95% CI: −1.46 to −0.54). Conclusions: This study found that individuals with reduced handgrip strength and handgrip strength asymmetry had an increased risk of cognitive impairment across various domains. Moreover, this association appears to be more pronounced among men than women. Incorporating these simple assessments into regular clinical practice improves the allocation of limited screening resources and timely clinical interventions in older adults.